2012
DOI: 10.1016/j.rppneu.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Função pulmonar em doentes obesos submetidos a cirurgia bariátrica

Abstract: Obesity is considered one of the most serious public health problems of the modern world. Because it alters the relationship between the lungs, chest wall and diaphragm, it is to be expected that it impacts on the respiratory function. In Portugal, there is not much data about the relationship between obesity and pulmonary function. The aim of this study was to characterize respiratory function in morbidly obese patients and to evaluate whether weight loss in patients submitted to bariatric surgery affects pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
4
0
6
Order By: Relevance
“…Guimarães, Martins and Santos, 26 evaluated the lung function of morbidly obese individuals and concluded that obesity influenced ERV and FRC. The authors explained that the reduction of ERV and FRC in obesity occurs due to mechanical changes in the chest wall, a decrease in total respiratory compliance, and reduced lung flow and volume.…”
Section: Discussionmentioning
confidence: 99%
“…Guimarães, Martins and Santos, 26 evaluated the lung function of morbidly obese individuals and concluded that obesity influenced ERV and FRC. The authors explained that the reduction of ERV and FRC in obesity occurs due to mechanical changes in the chest wall, a decrease in total respiratory compliance, and reduced lung flow and volume.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports a reduction of maximum pressure generated by the contraction of the ventilatory muscles due to the biomechanical disadvantage and an increase in respiratory work. The impairment in respiratory mechanics, characterized by a reduction of thoracic compliance due to the buildup of fat, a reduction of tidal volume and a consequent increase in respiratory rate, are positively correlated with the degree of obesity [34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Indicam também a redução da capacidade ventilatória em indivíduos com elevados níveis de gordura corporal (AGUIAR et al, 2012;BOSON;GARDENGHI, 2012;COSTA et al, 2003;GUIMARÃES;MARTINS;SANTOS, 2012;RASSLAN et al, 2004). Cabe ressaltar que estes estudos avaliaram a função pulmonar utilizando a espirometria e com o avaliado em repouso, enquanto que o trabalho analisou a capacidade cardiorrespiratória através do teste ergoespirométrico, considerando as medidas respiratórias diretas do analisador de gases VO2000.…”
Section: Resultsunclassified
“…A obesidade se caracteriza pelo acúmulo de tecido adiposo acima do recomendado e é considerada uma doença crônica não transmissível (BOSON; GARDENGHI, 2012;GUIMARÃES;MARTINS;SANTOS, 2012;HEYWARD, 2004;SALVE, 2006). As disfunções cardiometabólicas dos obesos, que afetam vários tecidos e/ou sistemas corporais, tornam os sujeitos mais suscetíveis ao desenvolvimento de doenças, como os problemas pulmonares (FRANÇA, 2004;OLIVEIRA et al, 2006;SALVE, 2006;SCIPIONI, 2010, TEIXEIRA et al, 2007.…”
Section: Fundamentação Teóricaunclassified